Barriers to home bowel cancer screening. Issue 10 (3rd June 2021) - Goodwin, Belinda C.; Myers, Larry; Ireland, Michael J.; March, Sonja; Ralph, Nicholas; Dunn, Jeff; Chambers, Suzanne; Aitken, Joanne
Abstract: Objective: To develop and test a psychometric instrument for measuring common barriers to completing and returning home bowel cancer screening kits. Methods: One hundred and ten items were reviewed by an expert panel ( n  = 15) and presented in an online cross‐sectional survey with 427 Australian adults. Exploratory factor analysis was used to identify an optimal factor solution of latent barrier types and aggregated factor scores were examined and compared between demographic groups. Results: Common barriers included having already been screened (32.3%), forgetting about the kit (24.4%), and a lack of planning (21.8%). Barriers reflecting hygiene concerns were also endorsed by over 15% of the sample. Four clear barrier types were evident reflecting disgust, avoidance, lack of autonomy, and physical difficulties. Conclusions: Findings support calls to apply multi‐faceted interventions strategies that address a broad range of barrier types, particularly that which encourage planning, and prompt and facilitate easy stool collection.